#UTOPia: Urogynecology Tag Ontology Project. Issue 9 (September 2021) - Davenport, Abigail; Hoang, Elizabeth; Jallad, Karl; Park, Amy J.; Fitzgerald, Jocelyn; Iglesia, Cheryl B.
Abstract : Objective: The objective of this study was to review and analyze the current social media status of urogynecology/female pelvic medicine and reconstructive surgery on Twitter and create a tag ontology. Methods: A "tag ontology" is a standardized list of hashtags used to organize specific subject matter within a social media platform. We used an online social media analytics tool, Symplur to identify tweets and hashtags related to #urogynecology between January 2018 and July 2020. Hashtags identified using Symplur were verified manually via Twitter inquiries and reviewed by urogynecology social medial influencers for external validation. The hashtags were selected based on frequency of use, social media influencer opinion, and clinical relevance. Results: We identified 6, 847 tweets and 2, 946 users. Our ontology includes 67 terms categorized into 5 groups (urinary, prolapse, anus/rectum, vulva, and other). Using "Symplur Rank, " the 2 top influencers included @FPMRS and @FPMRSJournal. Conclusions: Adaptation of a standardized hashtag ontology facilitates communication between providers and patients about pertinent health care issues. Our study has created a urogynecology-specific ontology based on 2018–2020 Twitter usage.